2022
DOI: 10.31083/j.rcm2309312
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oral Anticoagulants versus Vitamin K Antagonists for the Treatment of Left Ventricular Thrombosis: A Meta-Analysis

Abstract: Background: Vitamin K antagonists (VKAs) have been recommended as first-line anticoagulants for patients with left ventricular thrombosis (LVT). Direct oral anticoagulants (DOACs) are used as an alternative to the standard of care in anticoagulation. The aim of this meta-analysis was to compare the efficacy and safety of VKAs and DOACs in the treatment of patients with LVT. Materials and Methods: Studies were identified by searching the PubMed, Web of Science, and Embase. The main outcomes included stroke or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
3
2
0
Order By: Relevance
“…Based on the pooled analysis from 19 studies, we found that the observed stroke rates were significantly lower in the DOAC group, with a similar trend in composite events of stroke and systemic embolism between the DOAC and VKA arms. Our findings corroborated with the results from recently conducted similar studies comparing DOAC to VKA for the treatment of LVT 46,47,50 . DOACs are attractive in clinical practice because their use does not require monitoring of PT/INR levels as it is necessary with VKA.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Based on the pooled analysis from 19 studies, we found that the observed stroke rates were significantly lower in the DOAC group, with a similar trend in composite events of stroke and systemic embolism between the DOAC and VKA arms. Our findings corroborated with the results from recently conducted similar studies comparing DOAC to VKA for the treatment of LVT 46,47,50 . DOACs are attractive in clinical practice because their use does not require monitoring of PT/INR levels as it is necessary with VKA.…”
Section: Discussionsupporting
confidence: 90%
“…Our meta‐analysis is the most robust and up‐to‐date study, including all relevant studies. Given the robustness and largest size including 33 studies, our analysis showed significant differences between VKA and DOACs, which was not observed with prior small‐scale meta‐analyses by Huang et al, Condello et al, Chen et al, Kido et al, Li et al, Camilli et al, and scientific documents 3,46–51 . Based on our findings, it is advisable to use the DOAC over VKA to manage LVT, given the better efficacy (thrombus resolution) and safety (lower mortality, bleeding, and stroke rates) profile of DOACs.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…It also highlighted that in post-acute MI patients, the treatment with DOACs might be superior to VKA for the treatment of LV thrombus. The meta-analysis of Li et al confirmed previous results, and in addition, it showed that concomitant antiplatelet medication did not influence the risk of stroke or systemic embolism, thrombus resolution, and bleeding events [ 26 ].…”
Section: The Use Of Doacs In Patients With LV Thrombussupporting
confidence: 62%
“…In other patients, the size of the thrombus remained unchanged, and it was necessary to change the VKA to a DOAC or vice versa. However, it was shown that treatment switching does not change either the embolic or hemorrhagic risk, or the thrombus resolution rate [ 26 ]. Although the vast majority of available data are concordant regarding the higher efficiency and safety of DOACs compared to VKA in patients with post-acute MI LV thrombus, there are case reports of thrombi that are difficult to resolve, do not reduce their size, or even form under anticoagulation.…”
Section: The Use Of Doacs In Patients With LV Thrombusmentioning
confidence: 99%